Nivel de Conocimientos de las madres adolescentes primíparas en el cuidado del recién nacido - Nontol Rubio, Yeni Francisca (2019)
The present descriptive cross-sectional research study was conducted at the Leoncio Prado Hospital, Huamachuco District, with the objective of determining the level of knowledge that adolescent primiparous mothers have in newborn care. A sample consisting of 45 adolescent mothers was considered, and a questionnaire was used as an evaluation instrument. The analysis was carried out using descriptive statistics. The study concluded that 48.89% of adolescent mothers presented an average level of knowledge about newborn care. Finally, the only demographic variable that is associated with the level of knowledge is the origin (X2 = 12.36, p <0.01), while age and the degree of instruction are not associated with the level of knowledge (X2 = 1.93, p> 0.05), (X2 = 6.62, p> 0.05) respectively.